2022
DOI: 10.1002/casp.2637
|View full text |Cite
|
Sign up to set email alerts
|

Black students' experiences of “acceptable” racism at a UK university

Abstract: Our research, conducted with 30 Black students at a predominantly White institution, used mixed qualitative methods to investigate Black students' sense‐making of experiences that signalled their non‐belonging. All participants experienced both overt and covert racism including the n‐word, racist humour, and negative stereotyping; and this occurred in public and intimate spaces. Our reflexive thematic analysis centred on interactional dynamics that can explain how racism on campus is rendered acceptable; and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Considering this, gender-based discrimination and perceived non-German origin appear to be among the most prevalent grounds for discrimination at German universities. This is in line with the international literature that reports considerable levels of discrimination against these characteristics in the US [26,27,61] as well as in the UK [62,63].…”
Section: Discrimination Characteristicssupporting
confidence: 91%
“…Considering this, gender-based discrimination and perceived non-German origin appear to be among the most prevalent grounds for discrimination at German universities. This is in line with the international literature that reports considerable levels of discrimination against these characteristics in the US [26,27,61] as well as in the UK [62,63].…”
Section: Discrimination Characteristicssupporting
confidence: 91%
“…In contrast, the social identity approach conceptualises these dynamics as an intergroup process-between members of groups who occupy different status positions, not just in terms of formal power structures (place in the organisational hierarchy) but in terms of informal power structures, including alliances within the workplace and wider societal structures (e.g., gender, ethnicity, class; Ramsay et al, 2010). From this perspective, what matters about negative workplace interactions is not just that they make a person feel intimidated and excluded as an individual (Naezer et al, 2019); more crucially, they signal that one is not seen as a member of the ingroup, and sometimes do so in ways that make salient other group memberships that might be important to personal identity (e.g., gender, ethnicity) but that in this context mark one as 'other' or outgroup (Osbourne et al, 2023). Moreover, this group-based approach changes how we understand the phenomenon of peer to peer and subordinate to supervisor bullying (Rospenda et al, 1998); these are no less structured by power (e.g., based on gender or class) than the typical representation of supervisor to subordinate bullying.…”
Section: General Conceptual Frameworkmentioning
confidence: 99%
“…Rather, they are relational and interactional, and to positively experience one's identity, one needs to be recognised by others and have one's belonging to groups affirmed (Reicher, 2004;Tajfel, 1979). For example, previous research showed that Black students often felt that they were stereotyped by their peers as lacking intelligence (Osbourne et al, 2023), the consequences of which can lead to students limiting their involvement in class discussions (Cornell & Kessi, 2017). However, individuals are not simply passive to such negative experiences, making it important to consider how Black students, both collectively and individually, attempt to navigate interactions where identity denial and misrecognition are expected or anticipated.…”
Section: Identity and Belongingmentioning
confidence: 99%